Mimicking the brain: evaluation of St Jude Medical's Prodigy Chronic Pain System with Burst Technology. (March 2014) - De Ridder, Dirk; Vanneste, Sven; Plazier, Mark; Vancamp, Tim
Abstract : The Prodigy is a new type of internal pulse generator that controls the delivery of electrical stimuli to nervous tissue. It is capable of delivering burst stimulation, which is a novel waveform that consists of closely spaced high-frequency electrical impulses delivered in packets riding on a plateau, and followed by a quiescent period. Its inception was based on mimicking burst firing in the nervous system and usually delivered by unmyelinated fibers that uniformly have a motivational affective homeostatic function. It thereby targets a multimodal salience network, even though the stimuli are delivered at the level of the spinal cord. As such, it is specifically capable of influencing the affective/attentional components of pain. Burst stimulation was initially safely applied off-label to the auditory cortex for tinnitus, and later also to the spinal cord, the somatosensory cortex for neuropathic pain, subcutaneously for failed back surgery syndrome, and cingulate cortex for addiction and tinnitus.